2019
DOI: 10.1007/s10495-018-1508-1
|View full text |Cite
|
Sign up to set email alerts
|

Clotam enhances anti-proliferative effect of vincristine in Ewing sarcoma cells

Abstract: Objective: Current therapeutic strategies used in Ewing sarcoma (ES) especially for relapsed patients have resulted in modest improvements in survival over the past 20 years. Combination therapeutic approach presents as an alternative to overcoming drug resistance in metastatic ES. This study evaluated the effect of Clotam (Tolfenamic acid or TA), a small molecule and inhibitor of Specificity protein1 (Sp1) and survivin for sensitizing ES cell lines to chemotherapeutic agent, Vincristine (VCR). Methods: ES cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The combination of TA and VCR did not induce any cytotoxic effect in non-cancerous astrocyte cells, serving the purpose of this preliminary study. Recently, we demonstrated that TA and VCR combination did not induce toxicity in cardiomyocytes (H9C2 cells) at the concentrations that inhibited Ewing sarcoma cancer cell growth by 70%(Shelake et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of TA and VCR did not induce any cytotoxic effect in non-cancerous astrocyte cells, serving the purpose of this preliminary study. Recently, we demonstrated that TA and VCR combination did not induce toxicity in cardiomyocytes (H9C2 cells) at the concentrations that inhibited Ewing sarcoma cancer cell growth by 70%(Shelake et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Tolfenamic acid (TA) has been shown anticancer activity in several cancer models, inhibiting both tumor growth and angiogenesis. As a small molecule inhibitor, it induces the degradation of specificity proteins (Sps), leading to a decrease in expression of SVN in various in vitro and in vivo tumor settings such as pancreatic cancer cells [93,94], human medulloblastoma (MB) cell lines, a mouse xenograft model [95], Ewing sarcoma (ES) cells [96], and colon cancer cells [97]. Though these findings point to the use of TA as a potential cancer treatment, a clinical trial of TA in pancreatic cancer in 2014 was withdrawn without a published reason (NCT02159248).…”
Section: Small Molecule Inhibitors Of Svnmentioning
confidence: 99%
“…It is used to treat various pain-related ailments in humans and animals. 1,2 Recently, its anti-Alzheimer effect 3–8 and anticancer activity against various cancers have also been identified and reported by many workers, 9–26 which have significantly increased its clinical importance.…”
Section: Introductionmentioning
confidence: 99%
“…It is used to treat various pain-related ailments in humans and animals. 1,2 Recently, its anti-Alzheimer effect [3][4][5][6][7][8] and anticancer activity against various cancers have also been identied and reported by many workers, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] which have signicantly increased its clinical importance. TA (2-[(3-chloro-2-methylphenyl)amino]benzoic acid) is structurally similar to aminobenzoic acids and contains an amine group that is attached to the two benzoic acid rings (Fig.…”
Section: Introductionmentioning
confidence: 99%